2016
DOI: 10.1126/sciadv.1501371
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and predictive antibody repertoire profiling by molecular amplification fingerprinting

Abstract: A new experimental-bioinformatic method was developed for error and bias correction in high-throughput antibody sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 55 publications
2
146
0
Order By: Relevance
“…1C). Notably, the three "functional" V H s (V H 1-62-1, V H 2-6-8, and V H 7-2) not detected by HTGTS-Rep-seq also were not found by another high-throughput repertoire sequencing method (25), suggesting that they may actually be nonfunctional with respect to the ability to undergo V(D) J recombination. V H -to-DJ H rearrangements occur at the pro-B stage, with only one in three expected to be in-frame (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C). Notably, the three "functional" V H s (V H 1-62-1, V H 2-6-8, and V H 7-2) not detected by HTGTS-Rep-seq also were not found by another high-throughput repertoire sequencing method (25), suggesting that they may actually be nonfunctional with respect to the ability to undergo V(D) J recombination. V H -to-DJ H rearrangements occur at the pro-B stage, with only one in three expected to be in-frame (5).…”
Section: Resultsmentioning
confidence: 99%
“…Being DNA-based, HTGTS-Rep-seq also bypasses a major limitation of RNA-based methods for certain applications by quantitatively capturing the frequency of Ig rearrangements in a population regardless of their expression level or whether they are productive or nonproductive. Current means to address biases due to multiplex PCR or varying expression levels between cells include the use of universal identifiers (25,36,37) or single cell methods (38), but HTGTS-Rep-seq can accurately identify a population repertoire profile without the additional cost or steps of synthesizing primers with random barcodes, or sorting for single cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, mutations were most likely generated during the PCR amplification of the linear donor template despite the use of a high fidelity polymerase (KapaHiFi). Recent studies using high-throughput sequencing on PCR amplicons have shown that reproducible polymerase hotspot errors are more common than previously believed, even with high-fidelity polymerases2829. Therefore, the generation of long donor templates by PCR may result in erroneous variants, which would present a major problem for future therapeutic applications.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the earlier HTS data was produced in this way 101. This can be overcome using methods that incorporate UMIs at the reverse transcription step so that only one copy of each mRNA molecule is counted 102. This method could also be used to align copies of the same sequence to identify and remove sequencing errors in high read methods.…”
Section: Clonality Analysismentioning
confidence: 99%